Improving students’ English language skills through English Camp method for 3 days at Pondok Pesantren Syafi’i Akrom Pekalongan - Ifan Rikhza Auladi; Nani Hidayati; Putri Arifatul Ilmiyah; Alfiyyah Nur Kautsar; Monika Muhtiromi Maulidah; Nia Putri Rizki Alfitri; Sukma Putrawan (CV. Yudhistt Fateeh, 2026)
English language proficiency is one of the essential competencies that Islamic boarding school students (pesantren) should possess to meet the needs of global education and communication. However, English learning in Islamic boarding schools (pesantren) still faces several challenges, such as limited understanding, limited opportunities for language practice, and a lack of confidence in communicating in English. The purpose of this community service activity was to improve the English skills of female students through a three-day English Camp programme at the Syafi'i Akrom Islamic Boarding School in Pekalongan. The activity was held from November 14–16, 2025, with 50 participants. The learning process includes several stages: preparation, implementation, and evaluation. The experiential learning and play-based learning approaches are implemented through activities such as vocabulary games, role-play, speaking practice, interactive quizzes, and motivational sessions for learning English. Evaluation is conducted through observation of participants' participation, learning motivation, speaking confidence, and vocabulary mastery. The results of the activities show increased participant engagement in learning, increased confidence in using English, and increased vocabulary mastery related to daily activities at the Islamic boarding school. In addition, this activity successfully strengthens collaboration between universities and Islamic boarding schools in developing language skills by creating an interactive, communicative, and enjoyable learning atmosphere. The English Camp programme has proven to be an effective learning alternative for improving teachers' English skills.